The schizophrenia and gut microbiota: A bibliometric and visual analysis - Yang, Chao; Lin, Xiaoxiao; Wang, Xianteng; Liu, Huanzhong; Huang, Jinyu; Wang, Shuai (Frontiers in Psychiatry, 2022)
Background Many studies have explored the link between the gut microbiota and schizophrenia. To date, there have been no bibliometric analyses to summarize the association between the gut microbiota and schizophrenia. We aimed to conduct a bibliometric study of this association to determine the current status and areas for advancement in this field. Materials and methods Publications related to the gut microbiota and schizophrenia were retrieved from the Web of Science Core Collection (WoSCC). The WoSCC literature analysis wire and VOSviewer 1.6.16 were used to conduct the analysis. Results In total, 162 publications were included in our study. The publications generally showed an upward trend from 2014. A total of 873 authors from 355 organizations and 40 countries/regions contributed to this field. The leading authors were Timothy Dinan, John F Cryan, and Emily Severance. The leading institutions were Johns Hopkins University, the University College Cork, and the University of Toronto. The most productive countries were the United States (US), China, and Canada. In total, 95 journals contributed to this field. Among them, the top three productive journals were Schizophrenia Research, Progress in Neuro Psychopharmacology Biological Psychiatry, and Frontiers in Psychiatry. The important keywords in the clusters were gut microbiome, bipolar disorder, schizophrenia, antipsychotics, weight gain, metabolic syndrome, gut-brain axis, autism, depression, inflammation, and brain. Conclusion The main research hotspots involving the connection between schizophrenia and the gut microbiota were the characteristics of the microbiota composition in schizophrenia patients, the gut-brain axis, and microbial-based interventions for schizophrenia. The studies about the association between gut microbiota and schizophrenia are limited, and more studies are needed to provide new insights into the gut microbiota in the pathogenesis and treatment of schizophrenia.